Subwavelength Imaging: Near‐Zero Index: Optical Magnetic Mirror for Field Enhancement and Subwavelength Imaging Applications (Advanced Optical Materials 12/2015). Issue 12 (December 2015) - Choi, Soo Bong; Park, Doo Jae; Byun, Sun Jung; Kyoung, Jisoo; Hwang, Sung Woo
Abstract : D. J. Park, J. Kyoung, and co‐workers describe on page 1719 a strong‐field enhancement at subwavelength slit arrays fabricated on a near‐zero‐index material. In the image, yellow bars represent nanoslits made from gold with a gray plate indicating the near‐zero‐index substrate. The light is expressed as a semitransparent white color. The incident light is abruptly bent when it approaches the slit opening because of a funneling effect. The electric field inside the slit can be enhanced by orders of magnitude by the optical magnetic mirror effect of the near‐zero‐index material.